(untitled) (Nordic Journal of African Studies, 2005)
In prisons, there are short-term and long-term prisoners, guilty and innocent people. Common to all of them is, however, that they have come to prison. Prisons generally have a shortage of material goods and shortage of positive external stimuli. But one thing is not lacking there: time. And time is the thing that prisoners in different ways try to shorten. For example, they start making journeys of the mind, mental journeys. What are the events and factors that caused my journey to prison?